Distribution and ecology of economically important ticks on cattle, with special reference to the Eastern Cape Province, South Africa and Namibia - Nyangiwe, Nkululeko (Stellenbosch: Stellenbosch University, 2017)
Thesis (PhDAgric)--Stellenbosch University, 2017.